(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
A total of 18 species of endophytic fungi were isolated from Andrographis paniculata plant. The fungi were: Aspergillus flavus, A. niger, A. terreus, Cladosporium sp., Colletotrichum sp., Curvularia chonburiensis, Curvularia lycopersici, Fusarium solani, Fusarium udum, Fusarium sp. 1, Lasiodiplodia theobromae, Monodictys paradoxa, P. chrysogenum, P. oxalicum, Penicillium sp. 1, Penicillium sp. 2, Penicillium sp. 3, and Scytalidium lignicola. In summer, 18 species of fungi were isolated from A. paniculata while 13 fungal species were isolated in winter season. The highest value of Shannon and Simpson diversity index was found in the leaf in summer season and the lowest value in the stem in winter season. Maximum species richness of endophytic fungi was recorded in leaf in Margalef‘s index and Menhinick index in winter season. Minimum species richness of endophytic fungi was recorded in stem in Margalef’s index and Menhinick index in summer season. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 29-34